Motherwort Injection for Preventing Uterine Hemorrhage in Women With Induced Abortion: A Systematic Review and Meta-Analysis of Randomized Evidence - Xinyu, Xue; Xintong, Tang; Youping, Li; Feng, Wan; Jiajie, Yu (Frontiers in Pharmacology, 2022)
Objective: Motherwort injection (MI) is a modern patented injection extracted from motherwort (Leonurus japonicus Hoult). Empirical studies and systematic reviews have shown the benefits of motherwort injection for preventing postpartum hemorrhage after vaginal delivery and cesarean section. This study was conducted to explore the efficacy and safety of motherwort injection for women with the prevention of post-abortion uterine hemorrhage. Methods: A comprehensive literature search was conducted to identify RCTs regarding the effect of the use of motherwort injection in women after abortion. Data from trials were pooled by meta-analysis and a random-effects model was used to calculate the summarized relative risks (RRs) and their 95% confidence intervals (CIs). The grading of recommendations assessment, development, and evaluation (GRADE) methodology was used to access the quality of the evidence. Results: Nine trials with a total of 1,675 participants were identified. Overall, motherwort injection combined with oxytocin compared to oxytocin had a significantly lower blood loss within 2 hours (MD = −50.00, 95% CI −62.92 to −37.08, very low quality); lower blood loss within 24 h (MD = −50.00, 95% CI −62.92 to −37.08, very low quality); however, there was no significant difference between motherwort injection and oxytocin (24 h: MD: 0.72, 95% CI −7.76 to 9.20; 48 h: MD: −0.01, 95% CI −11.35 to 11.33; 72 h: MD: −1.12, 95% CI −14.39 to 12.15, very low quality). Compared with oxytocin or no intervention, both motherwort injection and motherwort injection combined with oxytocin had a significantly decreased duration of blood loss (MI vs. O: MD −2.59, 95% CI −4.59 to −0.60, very low quality; MI + O vs. O: MD −2.62, 95% CI -3.02 to −2.22, very low quality; MI + O vs. No intervention: MD: −1.80, 95% CI −2.28 to −1.33, low quality). Seven of nine included trials reported adverse event outcomes. Three cases were found in the motherwort injection group, and five induced abortion syndromes were found in the motherwort injection plus oxytocin group. 29 adverse events were reported in the oxytocin group instead. The recovery time of normal menstruation after abortion was significantly earlier in the group using motherwort injection compared with oxytocin (MDs −3.77, 95% CI −6.29 to −1.25, very low quality), and the endometrial thickness in the motherwort injection group was significantly different from that in the oxytocin group (MD: 2.24, 95% CI 1.58 to 2.90, very low quality). Conclusion: The results of this meta-analysis indicate prophylactic use of motherwort injection may reduce the risk of uterine hemorrhage in women after abortion, and more high-quality research is needed to confirm the efficacy and safety of motherwort injection in preventing uterine hemorrhage after abortion. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=274153, identifier CRD42021274153